Synthesis, structures and selective luminescence sensing of cobalt(II) and copper(II) coordination architectures with 5, 5'-(diazene-1, 2-diyl)diisophthalic acid and 1, 10-phenanthroline. Issue 8 (7th May 2021) - Hu, Dou-Dou; Wang, Jun-Jie; Hu, Bing-Qing; Cao, Meng-Ge; Li, Chao-Yang; Fu, Yi-Ran; He, Yu-Fei; Lin, Qian-Wen; Chen, Jing-Xia; Wang, Yu
Abstract: Co(II) and Cu(II) complexes, [Co2 (H2 L)2 (phen)2 (H2 O)4 ](H2 O)2 (1 ) and [Cu2 (L)0.5 (phen)2 Cl2 ]n (2 ) [H4 L = 5, 5'-(diazene-1, 2-diyl)diisophthalic acid, phen = 1, 10-phenanthroline], have been solvothermally synthesized by a mixed-ligand strategy and structurally characterized by elemental analyses, IR spectra and X-ray diffraction (XRD) analyses. Single crystal XRD analyses indicate that 1 and 2 exhibit a binuclear structure and a 1D chain structure, respectively. The results reveal that the coordination configuration of M(II) has a pivotal part in formation of final structures. Moreover, they can conditionally detect Fe 3+ through luminescence quenching. In addition, 1 can also detect Cr2 O7 2− ions in the absence of S 2− and H2 P2 O7 2− ions. Graphical Abstract: